Rancang Bangun Host Sistem Mini SCADA Untuk Pengontrolan Beban Trafo 20 KV Pada Gardu Induk - Ikhwanto, Ikhwanto -; Kusumoputro, R.A. Suwodjo; Azman, Novi (Jurnal Ilmiah Giga, 2013)
ABSTARCT. In this era of globalization, the needs of remote control systems is increasing, where the system used is more sophisticated. Similarly, when a transformer operator in electrical substations, which will control and monitor the load transformer 20 KV is still done by hand. This will result in less efficient and optimal performance of the operator. We need a system that can control remotely. To overcome these problems, hence designed "Host Mini SCADA systems for controlling the load on 20 KV transformer substations parent. With this system an operator can perform control and monitoring of the load transformer 20 KV, among others: Frequency, Current, Voltage, and Temperature. In addition, this system also can detect if the transformer is faulty. Monitoring and controlling performed remotely via SMS Gateway. This system consists of a PC (Personal Computer), which functions as process control and remote control units. GSM Modem serves to make the process of data transfer via SMS (Short Message Service). Software Visual Basic, a programming language used to create a program / software on Host mini SCADA system. Keywords: Host Mini Systems SCADA, GSM Modem, SMS Gateway.